(3GdJfejI hQSGdI GdLGeYI aj GdCda GdKGdKs - (3eMeO eUWai(B, (3GdCSYOs ((3HjQhJ(B:s (3GdeDSSI GdLGeYjI ddOQGSGJ hGdfTQ hGdJhRjY(B,s, 2000)
(3bVGjG aj GdJfejI hGdJNda , OhQ GdLGeYI aj ehGLgI JMOjGJ GdJfejIs
(3GdeQGLY U(B.193 (3GdedGMb U(B.206s
Keywords: (3GdJfejIs; (3GdLGeYIs